2020
DOI: 10.1186/s12913-020-4910-7
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of thyroid function tests and examinations in participants of a population-based study

Abstract: Background: Thyroid disorders are common in the adult German population. Little is known about guideline implementation in clinical practice and the prevalence of diagnostic procedures in ambulatory care. The study aims to investigate the use of thyroid hormone measurements, thyroid ultrasound, thyroid scintiscan and associated costs in ambulatory care at population level.Methods: Data were derived from two independent population-based cohorts of the Study of Health In Pomerania (SHIP). Ambulatory billing data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 23 publications
1
14
0
Order By: Relevance
“…Structural abnormalities of the thyroid gland, including nodules and goitre, are very common and often lead to repeated testing, including functional test, ultrasound follow-up and scintiscan, which may induce invasive procedures. Previous analyses of the SHIP cohort have shown that 6.8% (378/5552) of subjects had at least one ultrasound and 2.6% (146/5552) had at least one scintiscan within 1 year prior to the study examination based on billing data (20). The majority of structural abnormalities are asymptomatic, clinically irrelevant and malignancy developed in only a very small proportion (6,7).…”
Section: Clinical Meaning Of the Results And Comparison With Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…Structural abnormalities of the thyroid gland, including nodules and goitre, are very common and often lead to repeated testing, including functional test, ultrasound follow-up and scintiscan, which may induce invasive procedures. Previous analyses of the SHIP cohort have shown that 6.8% (378/5552) of subjects had at least one ultrasound and 2.6% (146/5552) had at least one scintiscan within 1 year prior to the study examination based on billing data (20). The majority of structural abnormalities are asymptomatic, clinically irrelevant and malignancy developed in only a very small proportion (6,7).…”
Section: Clinical Meaning Of the Results And Comparison With Literaturementioning
confidence: 99%
“…Once a thyroid nodule is detected, a cascade of follow-up examinations with moderate sensitivity and even worse, low specificity, is recommended to exclude thyroid cancer. In clinical practice, ignoring findings or systematic follow-ups is common (20). Once follow-up examinations are started, there is uncertainty when to discontinue.…”
Section: Clinical Meaning Of the Results And Comparison With Literaturementioning
confidence: 99%
“…For instance, around 10 million thyroid function tests are carried out each year in the UK with enormous variation in frequency across practices, 2 while in comparison about 30% of the adult German population have thyroid function taken in any one year. 3 This testing, arguably over-testing, is inextricably linked with diagnosis, and with over-diagnosis. For example, the median level of thyroid stimulating hormone (TSH) at which treatment is begun has fallen steadily to reach 7.9 mIU/l by 2009, 4 despite a dearth of evidence of benefit of treating patients with a TSH below 10 mIU/l.…”
Section: Increased Testingmentioning
confidence: 99%
“…These studies would further increase the knowledge on the pathways to the diagnosis of thyroid cancer and other thyroid disorders, to differentiate clinically relevant diseases from those with no impact on mortality [ 19 , 49 ]. In addition, they would contribute to evaluate adherence to evolving guidelines [ 5 , 7 , 50 ] and they should be used to reduce unnecessary medicalization of patients [ 51 ] and unnecessary costs for the healthcare system [ 23 , 52 , 53 ].…”
Section: Discussionmentioning
confidence: 99%